ChemInform Abstract: A Fortuitously Straightforward Synthesis of 4‐Acetoxy‐2‐propyltetrahydrothiophene. Issue 20 (April 2016) - Ma, Bianbian; Yang, Shaoxiang; Tao, Feiyan; Sun, Baoguo; Liu, Yongguo; Tian, Hongyu
Abstract: The title tetrahydrothiophene is synthesized by a three‐step procedure involving a known epoxidation step of 1‐hepten‐4‐ol and subsequent mesylation and acetoxylation‐ring closing reactions.